Sistema de gestión del talento humano y su incidencia en las estrategias organizativas de la “compañía de taxi ejecutivo” del Cantón Quevedo, año 2016. - Yépez Galeas, Lorenzo Enrique (2016)
The present investigation carries out the analysis and evaluation of the performance of the human talent management and as it affects the organizational strategies of the executive taxi company PRESTOCAR S.A., of the canton Quevedo in the year 2016, through conventional methods such as interviews and surveys. These methods were applied and analyzed to determine the problems encountered in the whole process investigated, since with these instruments it was possible to define in a concise way all the results for the final analysis, corresponding to the applicable suggestions. In the first chapter is the contextual framework of research where the whole problem of research is developed, the second chapter comprises theoretical and conceptual basis, the third chapter details the methodology of research, the fourth chapter shows the results obtained And the fifth chapter shows the conclusions and recommendations. As a first step is carried out a survey of users and drivers, to know in detail the current situation in the services offered by PRESTOCAR SA, as a second step is carried out a census to the administrators of the company and to culminate the research is developed a summary Of the company's SWOT analysis where it determines the current situation. The results obtained are of great importance for the company PRESTOCAR S.A., improve the low quality that is evident, in the customer service. The conclusions that are detailed in the end after having thoroughly analyzed all the results give us a clear idea of the real problem that was found in the research carried out in the company PRESTOCAR SA, this leads to make the respective recommendations being this the most important point Within the development, since they are the ones that show us all the possible applicable solutions to solve all the problems encountered.